2011
DOI: 10.1124/mol.111.075556
|View full text |Cite
|
Sign up to set email alerts
|

Xanthines Down-Regulate the Drug Transporter ABCG2 and Reverse Multidrug Resistance

Abstract: ABCG2 is an ATP-binding-cassette (ABC) transporter that confers multidrug resistance (MDR) to tumor cells by extruding a broad variety of chemotherapeutic agents, ultimately leading to failure of cancer therapy. Thus, the down-regulation of ABCG2 expression and/or function has been proposed as part of a regimen to improve cancer therapeutic efficacy. In this study, we found that a group of xanthines including caffeine, theophylline, and dyphylline can dramatically decrease ABCG2 protein in cells that have eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…21) has been shown to downregulate the expression of ABCG2 in cancer cell lines in a time-and dose-dependent and reversible way. 126 Also, theophylline and dyphylline decreased ABCG2 expression significantly in MCF-7/MX100 cells in a time-dependent, dose-dependent, and reversible manner. Caffeine treatment was shown to increase the retention of MX.…”
Section: Xanthinesmentioning
confidence: 87%
“…21) has been shown to downregulate the expression of ABCG2 in cancer cell lines in a time-and dose-dependent and reversible way. 126 Also, theophylline and dyphylline decreased ABCG2 expression significantly in MCF-7/MX100 cells in a time-dependent, dose-dependent, and reversible manner. Caffeine treatment was shown to increase the retention of MX.…”
Section: Xanthinesmentioning
confidence: 87%
“…As regards MCF-7, the line used in the present study, previous studies demonstrated the effect of caffeine on enhancing cell apoptosis caused by exposure to paclitaxel (14) and increasing the cytotoxic effect of alkylating drugs, such as cyclophosphamide (36). In addition, caffeine and other xanthines, including theophylline and dyphylline, significantly decreased the expression of the ABCG2 protein in the MCF-7/MX100 subline, which exhibits a high resistance to anti-breast cancer drugs (37).…”
Section: Discussionmentioning
confidence: 99%
“…1A) were utilized for these studies. During the course of our investigations on the regulation of ABCG2 expression by methylxanthines in these cells 18 we observed that both cell lines were more resistant to this class of compounds than their drug-sensitive parent lines. This result was unexpected, since methylxanthines are not ABCG2 substrates.…”
Section: Cells Expressing Abcg2 Are Less Sensitive To Nutrient Deprivmentioning
confidence: 99%
“…Western blot assays for the autophagy markers LC3B (this is the only isoform of LC3 tested, referred as LC3 in this study) and SQSTM1 were conducted according to the protocol described previously, 18 with specific modifications for LC3. Immunoblotting was accomplished using a rabbit monoclonal antibody against LC3 (1:1,000; Cell Signaling Technology, 2775) and immunoreactive proteins were visualized using an enhanced chemiluminescent system (Super Signal West Femto Chemiluminescent Substrate; Thermo Scientific, 34095) according to the manufacturer's recommendations.…”
Section: Western Blot Analysismentioning
confidence: 99%